Teaching korean as a foreign language: inputs to new normal pedagogy / Inero Valbuena Ancho - Inero, Valbuena Ancho (Universiti Teknologi MARA, Kedah, 2020)
What lessons can be shared from instructional practices in Korean language teaching? How can other teachers learn from these experiences? Given these reflections, how can one imagine the future of foreign language teaching as guided by reflective practices? The delivery of foreign language classes also needs to be revisited as the sudden shift to teaching and learning modality has created a great impact on instructional materials development, lesson delivery, assessment, and other functions. As a study employing critical reflection as a method, this paper uses the professional learning context of the researcher with teaching Korean as a foreign language in graduate school. Critical reflection is used to further positively contribute to ways and practices of teaching the course. Teaching Korean as a foreign language to graduate students is an experience filled with lessons worthy of examination. These lessons as a product of practice inform prospects with the end goal of refining classroom strategies. The experiences of teachers of Korean as a foreign language could serve as a springboard in critically revisiting practices and methodologies in the classroom.